Peafowl Production - Fatma Yenilmez (Turkish Journal of Agriculture: Food Science and Technology)
Peafowl is a common name of three species of the Phasianidae family. It is known as a sacred bird in many Asian countries and India that is the homeland of the peafowl. They live in groups and prefer cultivated areas and forests where they can find more food in nature. They feed on cereal grains, insects, fruits, leaves, seeds. It has a strong structure and adapts very well to different climates. Because of this feature can be produced anywhere in the world. There are commonly known three different types of peafowl. Blue (Indian) Peafowl (Pavo cristatus), Green Peafowl (Pavo muticus) and Congo Peafowl (Afropavo congoensis). The most recognizable species of them is the Indian Peafowl. Peafowl has always been the center of attention with its striking, bright and eye-catching colors on its body and long tail, and it is natural wonders. Therefore, they are especially indispensable members of zoos and ornamental gardens. Although peafowl are usually produced for their beautiful appearance, their meat is also very tasty and beneficial. This article is prepared to give brief information about peafowl.